Evaluation of the SpeeDx ResistancePlus® GC and SpeeDx GC 23S 2611 (beta) molecular assays for prediction of antimicrobial resistance/susceptibility to ciprofloxacin and azithromycin in Neisseria gonorrhoeae. (15th September 2020) - Hadad, Ronza; Cole, Michelle Jayne; Ebeyan, Samantha; Jacobsson, Susanne; Tan, Lit Yeen; Golparian, Daniel; Erskine, Simon; Day, Michaela; Whiley, David; Unemo, Magnus; ,
Abstract: Background: Accurate molecular assays for prediction of antimicrobial resistance (AMR)/susceptibility in Neisseria gonorrhoeae (Ng) can offer individualized treatment of gonorrhoea and enhanced AMR surveillance. Objectives: We evaluated the new ResistancePlus ® GC assay and the GC 23S 2611 (beta) assay (SpeeDx), for prediction of resistance/susceptibility to ciprofloxacin and azithromycin, respectively. Methods: Nine hundred and sixty-seven whole-genome-sequenced Ng isolates from 20 European countries, 143 Ng-positive (37 with paired Ng isolates) and 167 Ng-negative clinical Aptima Combo 2 (AC2) samples, and 143 non-gonococcal Neisseria isolates and closely related species were examined with both SpeeDx assays. Results: The sensitivity and specificity of the ResistancePlus ® GC assay to detect Ng in AC2 samples were 98.6% and 100%, respectively. ResistancePlus ® GC showed 100% sensitivity and specificity for GyrA S91 WT/S91F detection and 99.8% sensitivity and specificity in predicting phenotypic ciprofloxacin resistance. The sensitivity and specificity of the GC 23S 2611 (beta) assay for Ng detection in AC2 samples were 95.8% and 100%, respectively. GC 23S 2611 (beta) showed 100% sensitivity and 99.9% specificity for 23S rRNA C2611 WT/C2611T detection and 64.3% sensitivity and 99.9% specificity for predicting phenotypic azithromycin resistance. Cross-reactions with non-gonococcal Neisseria species were observed with both assays, but the analysis software solved most cross-reactions. Conclusions: The new SpeeDx ResistancePlus ® GC assay performed well in the detection of Ng and AMR determinants, especially in urogenital samples. The GC 23S 2611 (beta) assay performed relatively well, but its sensitivity, especially for predicting phenotypic azithromycin resistance, was suboptimal and further optimizations are required, including detection of additional macrolide resistance determinant(s).